Unusual Chair-Like G-Quadruplex Structures: Heterochiral TBA Analogues Containing Inversion of Polarity Sites - Antonella Virgilio; Luciano Mayol; Michela Varra; Aldo Galeone; Veronica Esposito (Journal of Chemistry)
Heterochiral oligodeoxynucleotides based on the thrombin binding aptamer sequence, namely, 5′gg3′-3′TT5′-5′ggtgtgg3′-3′TT5′-5′gg3′ (H1), 5′gg3′-3′TT5′-5′gg3′-3′TGT5′-5′gg3′-3′TT5′-5′gg3′ (H2), and 5′gGTTGgtgtgGTTGg3′ (H3), where lower case letters indicate L-residues, have been investigated in their ability to fold in G-quadruplex structures through a combination of gel electrophoresis, circular dichroism, and UV spectroscopy techniques. In H1 and H2 inversions of polarity sites have been introduced to control the strand direction in the loop regions. Collected data suggest that all modified sequences are able to fold in chair-like G-quadruplexes mimicking the original TBA structure.